NAVIGASI PRINSIP DASAR TEKNOLOGI PEMBELAJARAN: REKONSTRUKSI MULTIDIMENSIONAL MENUJU ERA KECERDASAN ARTIFISIAL YANG HUMAN-CENTRIC - Yudhi Hertanto; Happy Gustrin (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
Learning technology has transformed from merely a supporting instrument into a foundational architecture of modern education that reshapes learning processes and experiences. This article aims to analyze the fundamental principles of learning technology through four main dimensions, namely philosophical, sociological, juridical, and pedagogical, with a focus on the dynamics of education in Indonesia following the enactment of Permendikdasmen No. 13 of 2025. This study employs a qualitative method with a library research approach, utilizing various scientific sources, regulations, and relevant reports as the basis of analysis. The findings indicate a paradigm shift from instructional control toward learner facilitation, which requires the integration of technology in a human-centric manner. The results also reveal a paradox in the implementation of technology, where the acceleration of digitalization is not always accompanied by ethical readiness and equitable access. The Deep Learning approach, characterized by mindful, meaningful, and joyful learning, emerges as a potential solution to address these challenges, particularly in 3T (underdeveloped, frontier, and outermost) regions and in responding to the crisis of academic integrity caused by the misuse of artificial intelligence. This article recommends strengthening ethical digital literacy, developing locally adaptive technologies, and ensuring infrastructure equity as key prerequisites for the successful implementation of learning technology in Indonesia. ABSTRAK Teknologi pembelajaran telah bertransformasi dari sekadar instrumen pendukung menjadi fondasi arsitektur pendidikan modern yang membentuk ulang proses dan pengalaman belajar. Artikel ini bertujuan untuk menganalisis prinsip dasar teknologi pembelajaran melalui empat dimensi utama, yaitu filosofis, sosiologis, yuridis, dan pedagogis, dengan fokus pada dinamika pendidikan di Indonesia pasca pemberlakuan Permendikdasmen No. 13 Tahun 2025. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka yang memanfaatkan berbagai sumber ilmiah, regulasi, dan laporan relevan sebagai dasar analisis. Hasil penelitian menunjukkan adanya pergeseran paradigma dari kendali instruksional menuju fasilitasi pembelajar yang menuntut integrasi teknologi secara human-centric. Temuan juga mengungkap adanya paradoks dalam implementasi teknologi, yaitu percepatan digitalisasi yang tidak selalu diimbangi dengan kesiapan etika dan pemerataan akses. Pendekatan Deep Learning sebagai model pembelajaran yang mindful, meaningful, dan joyful menjadi salah satu solusi dalam menjawab tantangan tersebut, khususnya di wilayah 3T dan dalam menghadapi krisis integritas akademik akibat penyalahgunaan kecerdasan artifisial. Artikel ini merekomendasikan penguatan literasi digital berbasis etika, pengembangan teknologi adaptif lokal, serta pemerataan infrastruktur sebagai prasyarat utama keberhasilan implementasi teknologi pembelajaran di Indonesia.